Gender and Power in Shaping the News: A Critical Discourse Analysis Approach of the Divorce Case between Sheikh Mohammed Bin Rashid Al Maktoum and Princess Haya Al Hussain in the BBC (Journal of Natural Language and Linguistics, 2025)
The focal point of this research is to examine the role of gender and power in influencing the UK legal system by conducting a discourse analysis on the BBC news coverage of a royal divorce. BBC reported the case of Mohammed bin Rashid al-Maktoum v Princess Haya [2021] in six articles and portrayed the context that Princess Haya was in “fear for her life” and needed rescue through the court. These articles focused on reporting Sheikh’s negative reputation by mentioning his alleged kidnapping of his daughter, Sheikha Latifa, against her will to flee from the country. Although Princess Haya was unfaithful to her husband, however, it was not mentioned; instead, their marriage was noted as forceful. This portrayal led to the judge’s decision in Princess Haya’s favor in both divorce and children’s custody. It shows the significance of media in defining the narrative about a person underpinned by the framing theory. Media can shape the narrative about court cases and influence ruling outcomes.